2022
DOI: 10.3390/agronomy12123079
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Cr(VI) Toxicity and Improve Phytostabilization Potential of Vigna radiata Using a Novel Cr(VI) Reducing Multi-Stress-Tolerant Plant Growth Promoting Rhizobacterial Strain Bacillus flexus M2

Abstract: Chromium (Cr) is a toxic heavy metal discharged into the environment through various anthropogenic sources, which affects soil properties and fertility. Hence, an effective soil restoration strategy is the need of the hour. In this study, a potent Cr(VI)-reducing strain M2 was isolated from the rhizosphere of Zea mays L. grown in leather industrial effluent contaminated sites and identified as Bacillus flexus through 16S rDNA sequencing. Strain M2 exhibited strong tolerance to multi-stresses such as temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Srinivas Ravi has also demonstrated that Bacillus spp. can enhance soil fertility by releasing IAA under Cr (VI) stress [20]. Furthermore, another study has shown that these microbes play an active role in enhancing the productivity of various crops under the abiotic stress of Cr (VI) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Srinivas Ravi has also demonstrated that Bacillus spp. can enhance soil fertility by releasing IAA under Cr (VI) stress [20]. Furthermore, another study has shown that these microbes play an active role in enhancing the productivity of various crops under the abiotic stress of Cr (VI) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ravi et al [3], a potent rhizobacterial strain B. flexus M2 was characterized for its ability to reduce Cr(VI) under various environmental stressors. The strain exhibited tolerance to high temperatures, alkaline pH, NaCl, and drought conditions.…”
mentioning
confidence: 99%